Development of an educational tool for learning periodic table - Jani, Nor Akmalazura; Wan Khalid, Wan Elina Faradilla; Mohd Ruslan, Siti Zaharah (2025)
Learning the periodic table is essential in chemistry, yet many students struggle with understanding and memorizing it. With advancements in technology, education has become more accessible, making e-books a more convenient alternative to traditional textbooks. To support and enhance the learning process, the flipped e-book Beyond the Basics: An Exploration of the Periodic Table has been developed for primary, secondary, pre-diploma, and diploma students as an instructional tool. Designed using Canva, a user-friendly platform for creating professional educational materials, the ebook integrates engaging visuals and interactive content. Additionally, learning games are created using Wordwall, a game-based learning platform, to reinforce key concepts. The e-book is easily accessible via a shared link and Google Sites, ensuring convenience for students. This e-book introduces learners to the names, symbols, atomic numbers, and mass numbers of key elements from Group 1A(1) to 8A(18) and transition metals in a simplified manner. To emphasize the significance of these elements, real-world applications are included, helping students understand their relevance in daily life. The ADDIE Model is applied as the instructional design framework to ensure effective content delivery. In conclusion, integrating a flipped e-book approach with traditional learning methods enhances student engagement and understanding of the periodic table. Future developments will focus on creating more interactive e-books and educational games to further promote interest in Science, Technology, Engineering, and Mathematics (STEM) education.